JURIDICAL ANALYSIS OF CRIMINAL ASPECTS IN AGREEMENTS FOR THE TRANSPORTATION OF GOODS AND SERVICES USING SEA SHIPS - Erdi Steven Manurung; Parameshwara; Soerya Respationo; Erniyanti; Fadlan (RADJA PUBLIKA, 2024)
There are 3 (three) principles of carrier responsibility in transportation law, namely the first is the principle of responsibility based on fault (fault of liability), the second is the principle of responsibility based on presumption of liability, and the third is the principle of absolute responsibility. The carrier's responsibilities in the transportation law mentioned above apply to responsibilities that apply nationally and internationally. For all losses that may occur, the owner of the property that suffers loss can reduce or mitigate the loss, and the loss can even be borne by someone else as long as this is agreed upon in advance. An agreement that occurs between those who own goods because they are worried that they will suffer losses as a result of carrying out transportation due to the threat of danger at sea and those who are willing to bear the loss is called a (marine) insurance agreement. Based on the research results, it was found that Law no. 17 of 2008 concerning Shipping, what is meant by ship's seaworthiness in this Law is the condition of the ship that meets ship safety requirements, prevention of water pollution from ships, manning, loading lines, loading, welfare of the crew and health of passengers, legal status of the ship, management safety and prevention of pollution from ships, and safety management of ships for sailing in certain waters. Provisions regarding criminal acts in the field of shipping, contained in articles 284, up to article 336, Law No. 17 of 2008 concerning Shipping, which are used to facilitate understanding are divided into 2 (two) categories or sections, namely: Based on the Subject of the perpetrator and based on Responsibility criminal.